IL12B rs6887695 polymorphism and interaction with alcohol intake in the risk of ulcerative colitis in Japan. (July 2022) - Miyake, Yoshihiro; Tanaka, Keiko; Nagata, Chisato; Furukawa, Shinya; Andoh, Akira; Yokoyama, Tetsuji; Yoshimura, Naoki; Mori, Kenichiro; Ninomiya, Tomoyuki; Yamamoto, Yasunori; Takeshita, Eiji; Ikeda, Yoshio; et al.
Highlights: IL12B SNP rs6887695 was significantly associated with ulcerative colitis. Interaction between IL12B SNP rs6887695 and alcohol consumption was significant. Interaction between IL12B SNP rs6887695 and smoking was not significant. Abstract: Background: The interleukin (IL)-23/Th17 pathway plays a critical role in ulcerative colitis (UC). The IL-12p40 subunit, which is shared by IL-23 and IL-12, is encoded by the IL12B gene. The current case-control study investigated the association between IL12B SNP rs6887695 and the UC risk. Methods: There were 384 cases within 4 years of UC diagnosis and 661 controls who were enrolled. Adjustments were made for sex, age, pack-years of smoking, alcohol consumption, history of appendicitis, family history of UC, education level, and body mass index. Results: Subjects with the GG IL12B SNP rs6887695 genotype had a significantly increased risk of UC compared with those with the CC genotype (adjusted odds ratio [AOR], 1.60; 95% confidence interval [CI], 1.08–2.36). This positive association was also significant using the additive and recessive models (AOR, 1.25; 95% CI, 1.03–1.52; AOR, 1.50; 95% CI, 1.08–2.09, respectively). An independent inverse relationship was observed between ever alcohol consumption and the UC risk in those with the CC genotype while no significant association was found in those with at least one G allele ( P for interaction = 0.0008). Conclusions: IL12B SNP rs6887695 was significantly associated with UC. The influence of alcohol consumption might rely on rs6887695.